Is shared decision making an aspect of palliative care integration? An observation of collaboration between oncologists and palliative care professionals - Morgane Plançon; Ashley Ridley; Kristopher Lamore; Andréa Tarot; Alexis Burnod; François Blot; Isabelle Colombet (BMC Palliative Care)
Abstract Background Early palliative care interventions in oncology, as recommended by international oncology societies, promote patient understanding and support decision-making. At the same time, shared decision-making models are being developed to enhance patient participation as part of a new model of patient-physician relationship. For patients with palliative needs, this participation is essential and helps to avoid futile and aggressive treatments at the end of life. The aim of this study is to observe decision making during meetings between oncology and palliative care professionals, focusing particularly on the components of shared decision-making models, but also on the role played by palliative care professionals. Methods We conducted a non-participant observation of multidisciplinary meetings and outpatient clinic activities in two Comprehensive Cancer Centres in France. Field notes were then coded using thematic content analysis. Deductive analysis was conducted using the observation grid developed from Elwyn's three-talk model. Results Only a few elements of the different models of shared decision-making are apparent in the multidisciplinary meetings. Palliative care professionals emphasise the importance of involving patients and providing them with information about the advantages and disadvantages of different treatment options. However, patient involvement in decision-making remains difficult in daily practice. Decisions to discontinue oncological treatment are often driven by clinical and biological signs of terminal evolution rather than shared decision-making. Conclusions There are still cultural and organisational barriers to actual implementation of early integrated onco-palliative care. Promotion of shared decision making can be a strong lever of change which is frequently mobilised by palliative care teams.